Hubungan Tingkat Pengetahuan Dengan Perilaku Pengobatan Acne Vulgaris Di Kalangan Pelajar Sman 4 Bandar Lampung - Tri Wahyuni, Novita; Sari, Novita; Allesia, Eci (JFL : Jurnal Farmasi Lampung, 2023)
Acne vulgaris (AV) is a condition when the skin pores become clogged and cause the appearance of pus sacs on the skin causing inflammation. In general, Acne vulgaris is a teenage skin disease that most often occurs at the age of 15-18 years. The purpose of this study was to determine the relationship between the level of knowledge and acne vulgaris treatment behavior among adolescents of SMAN 4 Bandar Lampung. The type of research conducted is descriptive, analytical, cross-sectional with instruments in the form of questionnaires. The sample in this study was students of SMAN 4 Bandar Lampung. The sampling technique was carried out by random sampling with a total of 90 respondents in accordance with the inclusion criteria. Data analysis in this study used Chi-square testing techniques. The results of this study showed that the number of respondents with the female sex (74%) was more than men (26%), this result showed that women experienced acne vulgaris more often than men. and respondents experienced acne vulgaris the most at the age of 15 years (30%). The results showed the level knowledge of respondentd (54%) in yhe good category, while the level of respondent behavior (54%) in the medium category. The results of the correlation analysis test showed a relationship between the level of knoeledge and acne vulgaris treatment behavior with a significance value (p,001)<0,05.